1985
DOI: 10.1021/ac00286a008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thin-layer chromatographic adsorbates by Fourier transform infrared photoacoustic spectroscopy

Abstract: Fourier transform Infrared photoacoustic spectroscopy (FTIR-PAS) Is used to analyze substances deposited on thin-layer chromatographic (TLC) silica gel plates. In spectral regions of high silica gel absorption, little structural Information Is derived. Regions of lesser absorption provide Infrared spectral Information of the adsorbate and Interactions between adsorbed species and the silica gel substrate. Detection limits of 1 ¿tg are reported for photoacoustic analysis of caffeine deposited on silica gel. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Although this problem isfairlyserious, there is nodoubt that this method offers an effective means of identifying the components of complex mixtures. The sample size used in this experiment, i.e., 2-1 6 pg/component, is comparable to those previously reported for DR and photoacoustic [22] measurements inTLCIFTIR. It has been found that one thousand scans are required to be coadded before a high-quality spectrum is obtained from sub- Filespectraofthecomponentsof thetest mixtureinFigure6.Spectraare numbered to correspond with the peak no.…”
Section: Resultssupporting
confidence: 75%
“…Although this problem isfairlyserious, there is nodoubt that this method offers an effective means of identifying the components of complex mixtures. The sample size used in this experiment, i.e., 2-1 6 pg/component, is comparable to those previously reported for DR and photoacoustic [22] measurements inTLCIFTIR. It has been found that one thousand scans are required to be coadded before a high-quality spectrum is obtained from sub- Filespectraofthecomponentsof thetest mixtureinFigure6.Spectraare numbered to correspond with the peak no.…”
Section: Resultssupporting
confidence: 75%
“…Analysis of TLC spots by photoacoustic spectrometry (TLC/PAS) has been preferred over DRIFT analysis of strongly IR-absorbing samples (123). The spot containing 1-50 /Jig of the sample must be removed from the chromatoplate.…”
Section: B Instrumental Detection Modesmentioning
confidence: 99%
“…This approach is quick, convenient, and free of the risk of sample loss, since FTIR spectrum is directly obtained from the separated sample spot on a TLC plate. Subsequently, Griffiths et al [9,10], Zuber et al [11], Lloyd et al [12], and White [13] adopted various spectral techniques to develop a more practical in situ TLC/IR technique. However, the biggest problem of the in situ TLC/FTIR is that traditional TLC stationary phases, such as silica and alumina, exhibit strong background absorption that can bring about significant interference to sample identification.…”
Section: Introductionmentioning
confidence: 99%